Radiation-proof tempered glass and preparation method thereof

By adding molybdenum trioxide and alumina to tempered glass, a stable network structure is formed, and combined with spray cooling and surface etching film formation technology, the shortcomings of existing tempered glass in radiation protection and explosion-proof performance are solved, and high-strength, radiation protection and explosion-proof effects are achieved.

CN119874187APending Publication Date: 2025-04-25FOSHAN OUZE GLASS PRODUCTS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510224743.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing tempered glass has shortcomings in radiation protection and explosion-proof performance, and cannot effectively block electromagnetic radiation, and is prone to shattering when facing explosion or strong impact, affecting its application in high safety standards places.

Method used

By adding molybdenum trioxide and alumina during the glass preparation process, a stable network structure is formed, which enhances the mechanical properties and radiation absorption capacity of the glass, and forms a film through spray cooling and surface etching, improves the cooling strength and surface roughness of the glass, enhances its compressive strength and radiation resistance, and finally achieves radiation-proof, high-strength and explosion-proof effects by filling with thermoset polyurethane.

Benefits of technology

It significantly enhances the radiation, compression and explosion-proof performance of tempered glass, and improves its application value in high safety standards places.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005289813990000061
    Figure BDA0005289813990000061
  • Figure BDA0005289813990000071
    Figure BDA0005289813990000071
Patent Text Reader

Abstract

The invention discloses anti-radiation tempered glass and a preparation method thereof, and relates to the technical field of tempered glass. According to the invention, after novel glass is chemically tempered, spray cooling is utilized, so that the heat flux density of the glass surface is improved, the glass strength is enhanced, excessive etching is avoided, and active sites are provided for film adhesion; a film is formed through surface etching to form an irregular concave-convex structure, so that the anti-radiation effect is improved, the binding force between polyurethane and the glass is remarkably enhanced, and the compressive strength of the glass is improved; finally, polyurethane is filled in the two pieces of glass, so that the radiation-proof, high-strength and explosion-proof effects are achieved. Molybdenum trioxide and aluminum oxide are added in the preparation process of the novel glass, glass powder melting is promoted, glass gaps are filled with the molybdenum trioxide and aluminum oxide as network outer bodies, internal stress is reduced, the mechanical performance of the glass is enhanced, and the anti-radiation effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tempered glass, in particular to radiation-proof tempered glass and a preparation method thereof. Background Art

[0002] In modern architecture and daily life, tempered glass has become a widely used material due to its high transparency and beautiful appearance. It can be seen in curtain walls of high-rise buildings, doors, windows and furniture in homes. However, as people's requirements for quality of life and safety continue to improve, some performance shortcomings of tempered glass have gradually become apparent.

[0003] In the information age, electronic devices are everywhere, and electromagnetic radiation has become a health hazard that people are concerned about. In some places with high requirements for electromagnetic radiation protection, such as precision inspection rooms in hospitals and electronic equipment research and development laboratories, it is expected that tempered glass can play a certain role in radiation protection and provide protection for internal personnel and equipment. But in fact, ordinary tempered glass has limited ability in radiation protection and cannot effectively block various types of electromagnetic radiation, which greatly limits the use of tempered glass in these scenarios. In addition, in some industrial environments where there may be explosion risks, or public areas that are prone to accidental impacts, such as gas stations and entrances and exits of large shopping malls, once an explosion or strong impact occurs, tempered glass cannot maintain structural integrity as expected, and is very easy to break and splash, causing serious damage to personnel and surrounding facilities. The lack of this explosion-proof performance has seriously affected its application in places with high safety standards. Although tempered glass has a certain improvement in strength compared to ordinary glass, it still performs poorly when facing extreme mechanical stress. For example, under the influence of natural disasters such as strong winds and earthquakes, or under improper external force extrusion during transportation and installation, tempered glass is prone to cracking, deformation and other problems. This not only affects its aesthetics, but also reduces its reliability and durability, and increases the cost of subsequent maintenance and replacement. Summary of the invention

[0004] The object of the present invention is to provide a radiation-proof tempered glass and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing radiation-proof tempered glass, comprising the following preparation steps:

[0006] (1) 60-80 parts of quartz sand, 7-11 parts of molybdenum trioxide, and 20-30 parts of additives are mixed evenly, ground to a fineness of 500-700 μm, and then placed in a quartz crucible, melted at 1500-1600° C. for 2-4 hours, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace for annealing for 2 hours after molding, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new type of glass;

[0007] (2) Pour potassium nitrate into a tempering tank and heat it to melt, immerse the new glass in the molten salt of the tempering tank, heat it at 400-600° C. for 2-8 hours, take it out, cool it to 60° C. by spraying, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution at 65-85° C. for 2-4 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain the modified new glass;

[0008] (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a cavity in the middle, inject thermosetting polyurethane from the grouting hole, seal after filling and removing bubbles, and place in a 100°C oven for curing for 24 to 36 hours to obtain radiation-proof tempered glass.

[0009] Furthermore, the auxiliary agent in step (1) is prepared by mixing boric acid, aluminum oxide, sodium chloride and potassium carbonate in a mass ratio of 12:7:4:3.

[0010] Furthermore, the temperature of the muffle furnace in step (1) is 550-600°C.

[0011] Furthermore, the melting temperature of potassium nitrate in step (2) is 350-370°C.

[0012] Furthermore, the conditions for the spray cooling in step (2) are a spray distance of 200 mm, a spray pressure of 0.3-0.5 MPa, and a nozzle diameter of 1 mm.

[0013] Furthermore, the etching solution in step (2) is prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid, and ammonium nitrate in a mass ratio of 67:25:21:0.1.

[0014] Furthermore, the thickness of the cavity in step (3) is 0.75 to 1.55 mm.

[0015] Furthermore, the curing temperature of the thermosetting polyurethane in step (3) is 60-80°C.

[0016] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0017] The present invention increases the cooling intensity of the glass and the heat flux density on the surface of the glass by spray cooling after chemical tempering of the new glass, thereby increasing the temperature gradient inside and outside the glass, thereby increasing the surface compressive stress of the tempered glass and enhancing the strength of the glass. On this basis, during the cooling process, molybdenum and aluminum ions in the glass migrate to the surface, thereby avoiding excessive etching and providing active sites for film adhesion, thereby indirectly enhancing the adhesion. Then, the surface is etched to form a film to form an irregular concave-convex structure, and the light continuously changes its propagation direction at these concave-convex structures, so that the light that originally directly penetrates the glass is dispersed, thereby reducing the radiation intensity through the glass. At the same time, the surface roughness is increased, and more mechanical anchoring points are provided for the polymer, so that the polymer can be better embedded therein, thereby significantly enhancing the bonding force between the two and improving the compressive strength of the glass. Finally, polyurethane is filled into the two pieces of glass to achieve radiation protection, high strength, and explosion-proof effects.

[0018] Among them, the new type of glass promotes the melting of glass powder by adding molybdenum trioxide and aluminum oxide during the glass preparation process, and fills the glass gaps as a network outer body to reduce the internal stress caused by thermal expansion and contraction, thereby enhancing the mechanical properties of the glass. At the same time, the molybdenum element has a good absorption ability for rays, and is combined with aluminum oxide to connect with silicon oxygen tetrahedrons in the glass in the form of polyhedrons to form a stable network structure, which can effectively resist the impact of radiation particles and reduce structural damage, thereby achieving anti-radiation effects. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The test methods for various indicators of the radiation-proof tempered glass prepared in the following embodiments are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0021] Example 1

[0022] (1) 60 parts of quartz sand, 7 parts of molybdenum trioxide, and 20 parts of an additive prepared by mixing boric acid, aluminum oxide, sodium chloride, and potassium carbonate in a mass ratio of 12:7:4:3 are mixed uniformly, ground to a fineness of 500 μm, and then placed in a quartz crucible, melted at 1500° C. for 2 hours, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace after molding and annealed at 550° C. for 2 hours, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new glass;

[0023] (2) Pour potassium nitrate into a tempering tank and heat it to melt at 350°C, immerse the new glass in the molten salt of the tempering tank, heat it at 400°C for 2 hours, take it out, spray it to 60°C at a spray distance of 200mm, a spray pressure of 0.3MPa, and a nozzle diameter of 1mm, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid, and ammonium nitrate in a mass ratio of 67:25:21:0.1, stand it at 65°C for 2 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain the modified new glass;

[0024] (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a 0.75 mm thick cavity in the middle, inject thermosetting polyurethane with a curing temperature of 60 ° C from the grouting hole, seal after filling and removing bubbles, and place in a 100 ° C oven for curing for 24 hours to obtain radiation-proof tempered glass.

[0025] Example 2

[0026] (1) 70 parts of quartz sand, 9 parts of molybdenum trioxide, and 25 parts of an additive prepared by mixing boric acid, aluminum oxide, sodium chloride, and potassium carbonate in a mass ratio of 12:7:4:3 are mixed uniformly, ground to a fineness of 600 μm, loaded into a quartz crucible, melted at 1550° C. for 3 h, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace for annealing at 575° C. for 2 h after molding, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new glass;

[0027] (2) Pour potassium nitrate into a tempering tank and heat it to melt at 360°C, immerse the new glass in the molten salt of the tempering tank, heat it at 500°C for 5 hours, take it out, spray it to 60°C at a spray distance of 200mm, a spray pressure of 0.4MPa, and a nozzle diameter of 1mm, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid, and ammonium nitrate in a mass ratio of 67:25:21:0.1, stand it at 75°C for 3 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain the modified new glass;

[0028] (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a 1.15 mm thick cavity in the middle, inject thermosetting polyurethane with a curing temperature of 70°C from the grouting hole, seal after filling and removing bubbles, and place in a 100°C oven for curing for 30 hours to obtain radiation-proof tempered glass.

[0029] Example 3

[0030] (1) 80 parts of quartz sand, 11 parts of molybdenum trioxide, and 30 parts of an additive prepared by mixing boric acid, aluminum oxide, sodium chloride, and potassium carbonate in a mass ratio of 12:7:4:3 are mixed uniformly, ground to a fineness of 700 μm, and then placed in a quartz crucible, melted at 1600° C. for 4 hours, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace after molding and annealed at 600° C. for 2 hours, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new glass;

[0031] (2) Pour potassium nitrate into a tempering tank and heat it to melt at 370°C, immerse the new glass in the molten salt of the tempering tank, heat it at 600°C for 8 hours, take it out, spray it to 60°C at a spray distance of 200mm, a spray pressure of 0.5MPa, and a nozzle diameter of 1mm, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid, and ammonium nitrate in a mass ratio of 67:25:21:0.1, stand it at 85°C for 4 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain the modified new glass;

[0032] (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a 1.55 mm thick cavity in the middle, inject thermosetting polyurethane with a curing temperature of 80 ° C from the grouting hole, seal after filling and removing bubbles, and place in a 100 ° C oven for curing for 36 hours to obtain radiation-proof tempered glass.

[0033] Comparative Example 1

[0034] (1) 70 parts of quartz sand, 9 parts of molybdenum trioxide, and 25 parts of an additive prepared by mixing boric acid, aluminum oxide, sodium chloride, and potassium carbonate in a mass ratio of 12:7:4:3 are mixed uniformly, ground to a fineness of 600 μm, loaded into a quartz crucible, melted at 1550° C. for 3 h, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace for annealing at 575° C. for 2 h after molding, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new glass;

[0035] (2) Pour potassium nitrate into a tempering tank and heat it to melt at 360°C, immerse the new glass in the molten salt of the tempering tank, heat it at 500°C for 5 hours, take it out, cool it naturally to room temperature, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid, and ammonium nitrate in a mass ratio of 67:25:21:0.1, stand it at 75°C for 3 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain the modified new glass;

[0036] (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a 1.15 mm thick cavity in the middle, inject thermosetting polyurethane with a curing temperature of 70°C from the grouting hole, seal after filling and removing bubbles, and place in a 100°C oven for curing for 30 hours to obtain radiation-proof tempered glass.

[0037] Comparative Example 2

[0038] (1) 70 parts of quartz sand, 9 parts of molybdenum trioxide, and 25 parts of an additive prepared by mixing boric acid, aluminum oxide, sodium chloride, and potassium carbonate in a mass ratio of 12:7:4:3 are mixed uniformly, ground to a fineness of 600 μm, loaded into a quartz crucible, melted at 1550° C. for 3 h, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace for annealing at 575° C. for 2 h after molding, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new glass;

[0039] (2) Pour potassium nitrate into a tempering tank and heat it to melt at 360°C, immerse the new glass in the molten salt of the tempering tank, heat it at 500°C for 5 hours, take it out, spray it to 60°C at a spray distance of 200 mm, a spray pressure of 0.4 MPa, and a nozzle diameter of 1 mm, rinse it with deionized water and ethanol alternately for 3 times, and dry it to obtain the modified new glass;

[0040] (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a 1.15 mm thick cavity in the middle, inject thermosetting polyurethane with a curing temperature of 70°C from the grouting hole, seal after filling and removing bubbles, and place in a 100°C oven for curing for 30 hours to obtain radiation-proof tempered glass.

[0041] Comparative Example 3

[0042] (1) 70 parts of quartz sand, 9 parts of molybdenum trioxide, and 25 parts of an additive prepared by mixing boric acid, aluminum oxide, sodium chloride, and potassium carbonate in a mass ratio of 12:7:4:3 are mixed uniformly, ground to a fineness of 600 μm, loaded into a quartz crucible, melted at 1550° C. for 3 h, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace for annealing at 575° C. for 2 h after molding, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new glass;

[0043] (2) Pour potassium nitrate into a tempering tank and heat it to melt at 360°C, immerse the new glass in the molten salt of the tempering tank, heat it at 500°C for 5 hours, take it out, spray it to 60°C at a spray distance of 200 mm, a spray pressure of 0.4 MPa, and a nozzle diameter of 1 mm, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid, and ammonium nitrate in a mass ratio of 67:25:21:0.1, stand it at 75°C for 3 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain radiation-proof tempered glass.

[0044] Comparative Example 4

[0045] (1) 70 parts of quartz sand and 25 parts of an additive prepared by mixing boric acid, sodium chloride and potassium carbonate in a mass ratio of 12:4:3 are mixed evenly, ground to a fineness of 600 μm, put into a quartz crucible, melted at 1550° C. for 3 hours, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace for annealing at 575° C. for 2 hours after molding, cooled naturally to room temperature, cut, edged, cleaned and dried to obtain a new glass;

[0046] (2) Pour potassium nitrate into a tempering tank and heat it to melt at 360°C, immerse the new glass in the molten salt of the tempering tank, heat it at 500°C for 5 hours, take it out, spray it to 60°C at a spray distance of 200mm, a spray pressure of 0.4MPa, and a nozzle diameter of 1mm, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid, and ammonium nitrate in a mass ratio of 67:25:21:0.1, stand it at 75°C for 3 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain the modified new glass;

[0047] (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a 1.15 mm thick cavity in the middle, inject thermosetting polyurethane with a curing temperature of 70°C from the grouting hole, seal after filling and removing bubbles, and place in a 100°C oven for curing for 30 hours to obtain radiation-proof tempered glass.

[0048] Effect example

[0049] Table 1 below shows the performance analysis results of the radiation-proof tempered glass of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0050] Table 1

[0051]

[0052]

[0053] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Examples 1, 2, and 3, it can be found that the use of spray cooling increases the cooling intensity of the glass, increases the heat flux density on the glass surface, and increases the temperature gradient inside and outside the glass, thereby increasing the surface compressive stress of the tempered glass and enhancing the strength of the glass. On this basis, during the cooling process, the molybdenum and aluminum ions in the glass migrate to the surface, which prevents excessive etching and provides active sites for film adhesion, thereby indirectly enhancing the adhesion. By etching the surface to form a film, an irregular concave-convex structure is formed. The light continuously changes its propagation direction at these concave-convex structures, so that the light that originally directly penetrates the glass is dispersed, reducing the radiation intensity through the glass and increasing the surface roughness. More mechanical anchoring points are provided for the polymer, so that the polymer can be better embedded therein, the bonding force between the two is significantly enhanced, and the compressive strength of the glass is improved. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that by adding molybdenum trioxide and aluminum oxide during the glass preparation process, the melting of the glass powder is promoted, and the glass powder is filled in the glass voids as a network outer body, thereby reducing the internal stress caused by thermal expansion and contraction, thereby enhancing the mechanical properties of the glass. At the same time, the molybdenum element has a good absorption capacity for radiation, and is combined with aluminum oxide to connect with silicon oxygen tetrahedrons in the glass in the form of polyhedrons to form a stable network structure, which can effectively resist the impact of radiation particles, reduce structural damage, and achieve an anti-radiation effect.

[0054] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing radiation-proof tempered glass, characterized in that: The method comprises the following preparation steps: (1) 60-80 parts of quartz sand, 7-11 parts of molybdenum trioxide, and 20-30 parts of additives are mixed evenly, ground to a fineness of 500-700 μm, and then placed in a quartz crucible, melted at 1500-1600° C. for 2-4 hours, then taken out and cast into a graphite mold, and immediately transferred to a muffle furnace for annealing for 2 hours after molding, cooled naturally to room temperature, cut, edged, cleaned, and dried to obtain a new type of glass; (2) Pour potassium nitrate into a tempering tank and heat it to melt, immerse the new glass in the molten salt of the tempering tank, heat it at 400-600° C. for 2-8 hours, take it out, cool it to 60° C. by spraying, rinse it with deionized water and ethanol alternately for 3 times, place it in an etching solution at 65-85° C. for 2-4 hours, cool it naturally to room temperature, wash it with deionized water and dry it, and obtain the modified new glass; (3) After cleaning the two pieces of modified new glass, fix the four sides with film strips, leaving a cavity in the middle, inject thermosetting polyurethane from the grouting hole, seal after filling and removing bubbles, and place in a 100°C oven for curing for 24 to 36 hours to obtain radiation-proof tempered glass.

2. The method for preparing radiation-proof tempered glass according to claim 1, characterized in that: The auxiliary agent in step (1) is prepared by mixing boric acid, aluminum oxide, sodium chloride and potassium carbonate in a mass ratio of 12:7:4:

3.

3. The method for preparing radiation-proof tempered glass according to claim 1, characterized in that: The temperature of the muffle furnace in step (1) is 550-600°C.

4. The method for preparing radiation-proof tempered glass according to claim 1, characterized in that: The melting temperature of potassium nitrate in step (2) is 350-370°C.

5. The method for preparing radiation-proof tempered glass according to claim 1, characterized in that: The conditions for the spray cooling in step (2) are a spray distance of 200 mm, a spray pressure of 0.3-0.5 MPa, and a nozzle diameter of 1 mm.

6. The method for preparing radiation-proof tempered glass according to claim 1, characterized in that: The etching solution in step (2) is prepared by mixing deionized water, concentrated sulfuric acid, hydrofluoric acid and ammonium nitrate in a mass ratio of 67:25:21:0.

1.

7. The method for preparing radiation-proof tempered glass according to claim 1, characterized in that: The thickness of the cavity in step (3) is 0.75 to 1.55 mm.

8. The method for preparing radiation-proof tempered glass according to claim 1, characterized in that: The curing temperature of the thermosetting polyurethane in step (3) is 60-80°C.

9. A radiation-proof tempered glass, characterized in that: Prepared according to the method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-melting-point coloured glaze containing molybdenum trioxide and preparation method thereof

    CN103553331A

  • Display screen anti-radiation glass

    CN106186687A

  • Laminated glass with high barrier property and preparation method of laminated glass

    CN107417142A

  • Manufacturing method of frosted double-steel laminated glass

    CN116100930A

  • System for tempered glass

    KR1020110087774A